The role of macrophages polarization in predicting prognosis of radically resected gastric cancer patients. Issue 11 (27th November 2013) - Pantano, Francesco; Berti, Pierpaolo; Guida, Francesco Maria; Perrone, Giuseppe; Vincenzi, Bruno; Amato, Michelina Maria Carla; Righi, Daniela; Dell'Aquila, Emanuela; Graziano, Francesco; Catalano, Vincenzo; Caricato, Marco; Rizzo, Sergio; et al.
Abstract Tumour‐associated Macrophages (TAM) present two different polarizations: classical (M1) characterized by immunostimulation activity and tumour suppression; alternative (M2) characterized by tumour promotion and immune suppression. In this retrospective study, we evaluated the correlation between the two forms of TAM with survival time in radically resected gastric cancer patients. A total of 52 chemo‐ and radio‐naive patients were included. Two slides were prepared for each patient and double‐stained for CD68/NOS2 (M1) or CD68/CD163 (M2) and five representative high‐power fields per slide were evaluated for TAM count. The median value of the two macrophage populations density and the median value of M1/M2 ratio were used as cut‐off. Twenty‐seven patients with M1 density above‐the‐median had a significantly higher survival compared to those below the median. Twenty‐six patients with M1/M2 ratio above the median showed median OS of 27.2 months compared to 15.5 months of the patients below the median. No association between M2 macrophage density and patient's outcome was found. In multivariate analysis, M1/M2 was a positive independent predictor of survival. The M1 macrophage density and M1/M2 ratio, as confirmed in multivariate analysis, are factors that can help in predicting patients survival time after radical surgery for gastric cancer.